UPAYA MEMPERTAHANKAN BERAT ORGAN DALAM BABI LANDRACE PERSILANGAN DENGAN MEMBERIKAN LARUTAN ORALIT (G) SELAMA PENUNDAAN PEMOTONGAN - Budi Raharja, I G. N.; Ariana, I Nyoman Tirta; Oka, A. A. (Jurnal Peternakan Tropika; Volume 1 No. 1 Tahun 2013DO - 10.24843/EJPT.2013.v01.i01.p01)
This research that entitled “Effort to Maintain Inside Organ Weigth of Landrace Cross-breed Pig by Using Oralit Fluid While Delayed Slaughter” was done in two places, in Pig Farm Company PT. PuriAgrindo Indah (PAI) that adressed in Tunjuk village, Tabanan and Traditional slaughter place that adressed in Jln. Buluh Indah Gang IV/ 8 Br. Kerta Sari, Denpasar. The method of this research was using random group design (RAK) factorial pattern, that consist of two factor: the first one is the factor of time to raise the pig in bangsung (L) from 0 day (L0), 1 day (L1), 2 days (L2) and 3 days (L3), the second one was the doses of salt and sugar fluid that was given (G) that consist of without the given of salt and sugar fluid (G0), (150 g sugar + 15 g salt) / 1 liter of drink water (G1) and (300 g sugar + 30 g salt) / 1 liter of drink water (G2). The variabel that was observed is the weight of inside organ (heart, spleen, lungs, pancreas and intestinum). The result of this research shows that there was significant effect (P<0,05) in the weight of intestinum from L and G factor, but it is not really have significant effect to other inside organ. The interaction between G and L factor did not affect to all observed variabel. The weight of intestinum that was produced at L0, L1, L2, L3 was showed 4,079; 3,941; 3,631; 3,687 kg each, and at G0, G1, G2 showed 3,682; 3,917; 3,968 kg each. Based on this research that can be concluded that the placement of pigs inside basung for 3 days before it slaughter and the giving of oralit fluid, decreased the weight of intestinum but not affect other organs, meanwhile the interaction between G and L factor was not affect all observed variabel either. Key words: pig, sugar-salt solution, slaughtering delays, and weight of organs in pigs
Keywords: pig, sugar-salt solution, slaughtering delays, and weight of organs in pigs